Global and local economic impacts of climate change in Syria and options for adaptation - Breisinger, Clemens; Zhu, Tingju; Al-Riffai, Perrihan; Nelson, Gerald C.; Robertson, Richard D.; Funes, José; Verner, Dorte (International Food Policy Research Institute, 2011)
There is broad consensus among scientists that climate change is altering weather patterns around the world. However, economists are only beginning to develop tools that allow for the quantification of such weather changes on countries' economies and people. This paper presents a modeling suite that links the downscaling of global climate models, crop modeling, global economic modeling, and subnational-level computable equilibrium modeling. Important to note is that this approach allows for decomposing the potential global and local economic effects on countries, including various economic sectors and different household groups. We apply this modeling suite to Syria, a relevant case study given the country's location in a region that is consistently projected to be among those hit hardest by climate change. Despite a certain degree of endogenous adaptation, local impacts of climate change (through declining yields) are likely to affect Syria beyond the agricultural sector and farmers and also reduce economy-wide growth and incomes of urban households in the long term. The overall effects of global climate change (through higher food prices) are also negative, but some farmers can reap the benefit of higher prices. Combining local and global climate change scenarios shows welfare losses across all rural and urban household groups of between 1.6 - 2.8 percent annually, whereas the poorest household groups are the hardest hit. Finally, while there is some evidence that droughts may become more frequent in the future, it is clear that even without an increase in frequency, drought impacts will continue to put a significant burden on Syria's economy and people. Action to mitigate the negative effects of climate change and variability should to be taken on the global and local level. A global action plan for improving food security and better integration of climate change in national development strategies, agricultural and rural policies, and disaster risk management and social protection policies will be keys for improving the resilience of countries and people to climate change.